Spectroscopic and Antibacterial Studies of Mixed Ligand Complexes of Transition Metal (II) Ions with Sulfadoxine and 1,10- Phenanthroline - Al-Qadasy, Mohammed K; Al-Azab, Fathi M; Al-Maqtari, Maher A; Jamil, Yasmin Mosa’d Saeed (PSM Biological Research, 2018)
The mixed ligand complexes of Co(II), Ni(II) and Cu(II) with Sulfadoxine and 1,10-phenanthroline were synthesized and characterized by elemental analysis, Infrared (IR), mass spectrometry, 1H-NMR, and Ultraviolet (UV) spectroscopy. Some physical parameters were obtained using molar conductance measurement and melting point determination. Based on the analytical and spectroscopic data, the complexes were proposed to have the formula [M L1 L2 Cl2].nH2O, where M= Co, Ni or Cu; L1= sulfadoxine, L2=1,10- phenanthroline, n = 0 and 2. The spectroscopic data showed that sulfadoxine coordinated through (N-H) and (O=S=O), while1,10- phenanthroline coordinated through two nitrogen atoms making them bidentate ligands. The kinetic and thermodynamic parameters such as: activation energy (Ea), enthalpy of reaction (?H*), entropy change (?S*) and free energy change (?G*) were estimated from the differential thermal analysis curves. Free ligand 1,10-phenanthroline showed antibacterial activity, but sulfadoxine had no effect and all complexes showed antibacterial activity.